Correlation between Colon Polyps and Metabolic Syndrome and HP Infection Status - Lijuan Huang; Lihong Wu; Qiaohua Qiao; Lizheng Fang (Gastroenterology Research and Practice)
Background. This study investigated the relationships among the characteristics of colon polyps and potential risk factors, including metabolic condition, CEA level, uric acid level, and Helicobacter pylori (Hp) infection status. Method. Clinical data from patients who received colonoscopy were collected and analyzed, including patients’ gender, age, polyp pathology, metabolic syndrome (MS) status, CEA level, uric acid level, and Hp infection status. Patients were divided into a polyp group and a control group based on whether they presented with colon polyps. Then, clinical data were compared between the two groups to identify any differences between the groups and their relationships to colon polyps. Result. Compared with the control group, the polyp group had significant differences in patient gender, body mass index (BMI), waistline, blood pressure, fasting blood glucose level, blood lipid level, and uric acid level (p<0.05), but there were no significant differences in LDL and CEA levels (p>0.05). Patients with MS or a uric acid level>340 mg/dl had a greater tendency to develop colon polyps but this was not statistically significant. Conclusion. The incidence of colon polyps may be associated with MS and uric acid levels, but further studies are warranted to confirm this conclusion.